Prenatal, Obstetric, Neonatal Outcomes and Contraceptive Behaviors in Women with Four or More Pregnancies - Akay, Aysen; Yanikkerem, Emre (International Journal of Child Health and Nutrition, 2017)
Background: The aim of the population-based study was to determine prenatal, obstetric, neonatal outcomes and contraceptive behaviors in women with four or more pregnancies. Methods: This study was conducted with women (n=294) using a questionnaire in two family centers of Manisa, Turkey where the fertility rate was high. Results: In the study, the mean number of pregnancies was 5.6±1.5. Loving children, willing to have a larger family and to have a male child were determined the main reasons of extreme fertility. Although 93.2% of women did not desire to have children in the future, only 43.3% of them used a birth control method. The rates of gestational diabetes, hypertension, depression, physical violence, lower weight of baby, risk of miscarriage, preterm birth and cesarean section were higher in the women with more pregnancies. Conclusions: It is very important to provide women with more pregnancies who had unmet need with client-centered counseling to encourage them to use more effective methods.